Exposure-Response Modeling to Support Dosing Selection for Phase IIb Development of Kukoamine B in Sepsis Patients - Wang, Huanhuan; Hu, Xiaoyun; Wang, Teng; Cui, Cheng; Jiang, Ji; Dong, Kai; Chen, Shuai; Jin, Chunyan; Zhao, Qian; Du, Bin; Hu, Pei (Frontiers in Pharmacology, 2021)
Aim: Kukoamine B was a developed novel drug that targeted both LPS and CpG DNA in the treatment for sepsis. To optimize dosing selection for Phase IIb clinical trial, exposure- response model need be built based on the data of sepsis patients from Phase IIa clinical trial. Methods: SOFA score was selected as the biomarker of pharmacological effect in sepsis patients, Exposure-Response model was built through linking AUCss to pharmacological effect (SOFA score). The sequential model approach was utilized in our strategy for model development. Pharmacological effect of basic therapy was described using placebo model. Pharmacological effect of kukoamine B was driven by a latent variable that was described indirect response (IDR) model. Model validation was performed by goodness of fit (GOF) and visual predictive check (VPC). Finally, simulation was performed to assess the appropriateness of the proposed dose regimen. Results: Exposure-response model including pharmacological effect of basic therapy were successfully developed by nonlinear mixed-effect modeling approach in sepsis patients. Model validation showed that the developed model can well describe the observed data and can be simulated on different dose regimen. Conclusion: For the first time, we built exposure-response model that characterized pharmacological effect of kukoamine B administration in sepsis patients from ICU undergoing basic therapy. 0.24mg/kg dose regimen was finally recommended for Phase IIb development of kukoamine B in sepsis patients based on modelling and simulation results.